ISLAM DAN PROBLEM PEMIKIRAN: Fokus Kajian Ekonomi - Yuana Tri Utomo Utomo; Braham Maya Baratullah (Kopertais Wilayah III Yogyakarta, 2022)
Islam commands man to use his thinking. Human thinking very often becomes biased when humans interact to meet the needs of their daily lives. This article aims to describe the role of Islamic teachings in solving problems of human thought, especially focusing on economic thinking. This article is a form of qualitative research report with a simple literature study. Data sources are taken from references related to research topics in the form of books, especially those related to Islamic economics and teachings, several scientific journals that have been published and indexed nationally and internationally. The method of analysis used in this article is critical analysis, which is a criticism of some thoughts in the economic context that have developed in the social history of society with Islamic teachings so as to give birth to the concept of Islamic economics. This article conveys the results of research that the economic damage that occurs today is due to the application of economic concepts that originated from the economic thinking of capitalism. The economic thinking of capitalism does not actually depart from the reality of right thinking so that it becomes biased. The economic thinking of capitalism departs from the lusts of human gluttony. The fundamental criticism of economic problems that occurs is carried out on the principle of wrong thinking, which is to deny the role of religion in the economic regulation of society. The solution to this economic problem is to present an Islamic economy, that is, an economy that does not deny the role of religion, in this case it is Islam. The recommendations of this article require further research that examines Islamic economics and its branches of thought. Keyword: Problem Pemikiran, Islam, Kapitalisme gagal, Ekonomi Islam